The Influence of Teacher Leadership and Classroom Management Skills on the Learning Behavior of Grade VI Students at Serdang State Elementary School - Nurhadijah, Lidia; Hia, Era Era; Setiawan, Temmy (IJOSPOL - International Journal of Social, Policy and Law, 2026)
This study aims to determine the effect of teacher leadership and classroom management skills on the learning behavior of sixth-grade students at Serdang Wetan Public Elementary School, both partially and simultaneously. This study used a quantitative approach with a survey method. The population in this study was all sixth-grade students at Serdang Wetan Public Elementary School, totaling 30 students, who were also used as research samples using a non-probability sampling technique. The data collection technique was carried out by distributing questionnaires to respondents. The data analysis technique used was multiple linear regression analysis with the help of the SPSS 24 program. Data validity was tested through the t-test (partial) and F-test (simultaneous). The results of the study indicate that (1) partially, teacher leadership has a positive and significant effect on the learning behavior of sixth-grade students at Serdang Wetan Public Elementary School, (2) partially, classroom management skills have a positive and significant effect on student learning behavior, (3) simultaneously, teacher leadership and classroom management skills have a positive and significant effect on student learning behavior. Based on these results, it can be concluded that teacher leadership and classroom management skills, both partially and simultaneously, have a significant effect on the learning behavior of sixth-grade students at Serdang Wetan Public Elementary School